Dipeptidyl peptidase-4 inhibitory potentials of Glycyrrhiza uralensis and its bioactive compounds licochalcone A and licochalcone B: An in silico and in vitro study - Shaikh, Sibhghatulla; Ali, Shahid; Lim, Jeong Ho; Chun, Hee Jin; Ahmad, Khurshid; Ahmad, Syed Sayeed; Hwang, Ye Chan; Han, Ki Soo; Kim, Na Ri; Lee, Eun Ju; Choi, Inho (Frontiers in Molecular Biosciences, 2022)
Type 2 diabetes mellitus (T2DM) is a growing global public health issue, and dipeptidyl peptidase-4 (DPP-4) is a potential therapeutic target in T2DM. Several synthetic anti-DPP-4 medications can be used to treat T2DM. However, because of adverse effects, there is an unmet demand for the development of safe and effective medications. Natural medicines are receiving greater interest due to the inherent safety of natural compounds. Glycyrrhiza uralensis (licorice) is widely consumed and used as medicine. In this study, we investigated the abilities of a crude water extract (CWE) of G. uralensis and two of its constituents (licochalcone A (LicA) and licochalcone B (LicB)) to inhibit the enzymatic activity of DPP-4 in vitro and in silico. In silico studies showed that LicA and LicB bind tightly to the catalytic site of DPP-4 and have 11 amino acid residue interactions in common with the control inhibitor sitagliptin. Protein-protein interactions studies of LicA-DPP4 and LicB-DPP4 complexes with GLP1 and GIP reduced the DPP-4 to GLP1 and GIP interactions, indicated that these constituents might reduce the degradations of GLP1 and GIP. In addition, molecular dynamics simulations revealed that LicA and LicB stably bound to DPP-4 enzyme. Furthermore, DPP-4 enzyme assay showed the CWE of G. uralensis, LicA, and LicB concentration-dependently inhibited DPP-4; LicA and LicB had an estimated IC50 values of 347.93 and 797.84 μM, respectively. LicA and LicB inhibited DPP-4 at high concentrations, suggesting that these compounds could be used as functional food ingredients to manage T2DM.